Elucidating charge transport mechanisms in cellulose-stabilized graphene inks. Issue 43 (13th August 2020) - de Moraes, Ana C. M.; Obrzut, Jan; Sangwan, Vinod K.; Downing, Julia R.; Chaney, Lindsay E.; Patel, Dinesh K.; Elmquist, Randolph E.; Hersam, Mark C.
Abstract : Thin-films derived from solution-processed graphene inks that use ethyl cellulose as a polymer stabilizer show mixed metallic-semiconducting charge transport with high charge carrier mobility. Abstract : Solution-processed graphene inks that use ethyl cellulose as a polymer stabilizer are blade-coated into large-area thin films. Following blade-coating, the graphene thin films are cured to pyrolyze the cellulosic polymer, leaving behind an sp 2 -rich amorphous carbon residue that serves as a binder in addition to facilitating charge transport between graphene flakes. Systematic charge transport measurements, including temperature-dependent Hall effect and non-contact microwave resonant cavity characterization, reveal that the resulting electrically percolating graphene thin films possess high mobility (≈160 cm 2 V −1 s −1 ), low energy gap, and thermally activated charge transport, which develop weak localization behavior at cryogenic temperatures.